A study comparing the change in drug utilization pattern in medical intensive care unit of a tertiary care hospital in seven years - Karve, Ashwini V.; Chaure, Mayur M. (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Medical intensive care unit is a type of intensive care unit that takes care of a range of medical illnesses with patients who are seriously ill and/or suffer from severe chronic illnesses. These patients are usually prescribed multiple drugs. Use of antimicrobial agents and injectable medications in setting of MICU is high as compared with other class of drugs and other hospital settings respectively. Periodic evaluation of drug utilization pattern needs to be done to enable suitable modifications in prescription of drugs to increase the therapeutic benefit and decrease the adverse effects. There could be changes in drug utilization pattern due to changes in disease pattern, development of newer drugs, resistance to antimicrobial agents. Hence comparison of past and present data needs to be done to find out the changes that occurred in drug utilization pattern over the years. Methods: Data was collected from June 2021 to Dec 2021 for prospective arm and June 2014 to December 2014 for retrospective arm was obtained from MICU of tertiary care hospital and Medical Record Department. Drug utilization pattern was analysed and compared with appropriate statistical tests. Results: Most common cause of MICU admission was infective diseases (71% and 67% respectively in retrospective and prospective arm). The drug prescribed frequently was pantoprazole and antimicrobial was ceftriaxone in both the study arms. Half of the drugs were prescribed by generic names in both arms. Conclusions: There was no change observed in drug utilization pattern and disease pattern in patients admitted to medical intensive care unit over the years in our institute.